VETERINARY AND SANITARY INSPECTION OF MEAT AND INTERNAL ORGANS IN SHEEP ECHINOCOCCOSIS (LITERATURE REVIEW) - Ilashovich, Rasulov O‘tkir; Elmurodovich, Achilov Odil; qizi, Boymuratova Xonzoda Sharofiddin (Research Focus International Scientific Journal, 2026)
This study analyzes the impact of echinococcosis in sheep on the quality of meat and internal organs, as well as the specifics of their evaluation during veterinary and sanitary inspection, based on a review of scientific literature. The works of domestic and foreign researchers were examined, covering the etiology, pathogenesis, and epidemiological features of the disease. Particular attention is given to the effect of echinococcosis on the sanitary quality of meat products. Based on the literature review, key aspects of detecting affected organs, their veterinary-sanitary assessment, and disposal methods in accordance with current regulatory requirements are summarized.